Economic effciency of law in criminal cases - Puczkowski, Benedykt; Bylińska, Marta (Przegląd Prawno-Ekonomiczny, 2012)
Streszczenie dostępne wyłącznie w języku angielskim: Economical analysis of law is an issue brought up both in the legal environment as well as amongst economists and is an essential problem connected with the assessment of the law effectiveness. The problems of economical analysis of law and the influence and effects of law economisation on its efficiency have been discussed in the article. Verification of the hypothesis that some criminal cases conductedby courts in Poland are ineffective has been carried out the basis of costs incurred in criminal proceedings. Three case studies from research material collected on the basis of court records have been analysed. The conclusions referring to the effectiveness of the criminal law have been drawn basing on the results of analysis carried out.